Q: What is 9x plus 27 equals 6x plus 66?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x=4

-6x-66=66 First, add 66 to both sides to isolate the variable -6x=132 Then, divide by -6 and x=-22

6x+3=27 6x=24 (subtract 3 from each side) x=4 (divide both sides by 6)

(9,6)

6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.

Related questions

no

6x-14x+16=27+11 answer: 4

x=4

-6x-66=66 First, add 66 to both sides to isolate the variable -6x=132 Then, divide by -6 and x=-22

6x+3=27 6x=24 (subtract 3 from each side) x=4 (divide both sides by 6)

(9,6)

6x+x = 7x

6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.

-6x

324

x2 +6x = 27 x2 + 6x - 27 = 0 x2 + 9x - 3x - 27 = 0 x(x + 9) - 3(x + 9) =0 (x - 3)(x + 9) = 0 So x can equal 3 or -9.

x=10